THE IMPORTANCE OF THE HERITAGE OF EASTERN SCHOLARS IN SHAPING ECOLOGICAL CULTURE AMONG SCHOOL STUDENTS IN THE CONTEXT OF ECOLOGICAL GLOBAL - Azamova Sitora Ayonovna (Scholar Express Journal, 2025)
Today, one of the most important tasks facing humanity is to preserve natural resources in their original state for future generations. One of the most effective ways to solve this problem is to educate the younger generation to become nature-loving individuals with ecological culture. In this process, using the scientific heritage of Eastern thinkers yields effective results.
Keywords: ecology; consciousness; ecological globalization; ecological culture